The Role of Support Leg Kinematics in Ball Velocity and Spin Across Competitive Levels and Leg Preference - Yecheng Zhang; Archit Navandar; Enrique Navarro (Applied Sciences, 2025)
This study examines the impact of support leg kinematics on kicking performance and its direct relationship with ball velocity and spin. Seventy-eight players performed maximal instep kicks each with their preferred and non-preferred leg, which were recorded with a three-dimensional motion capture system. Linear mixed models were used to analyze the effects of discrete data of lower limb on ball velocity and spin. Professional male players exhibited significantly smaller hip internal-external rotation range of motion (ROM) and angular velocity compared to other groups (p < 0.05). In professional players, the preferred leg kicks showed greater knee flexion-extension ROM, flexion angular velocity, and extension angular velocity than the non-preferred leg kicks (p < 0.01). Regression analysis revealed that hip and knee extension angular velocities, as well as knee flexion-extension ROM, positively influenced kicking performance, while hip adduction-abduction ROM had a negative impact. These findings emphasize the critical role of the support leg in modulating ball velocity, ball spin, and stability during instep kicking. Training should prioritize hip and knee extension strength for power generation and frontal plane stability for postural control. This study offers novel insights into support leg kinematics across competitive levels, with implications for coaching and performance enhancement. Future research should explore phase-specific support leg dynamics during kicking.